CXCL8 modulates M0 macrophage proliferation and polarization to influence tumor progression in cervical cancer - Xiyan Zhao; Li Yang; Jigang Pan; Zhirui Zeng; Tuo Zhang; Yushi Yang; Jingjing Zhang; Tengxiang Chen; Ziwen Xiao; Wei Pan (Scientific Reports)
Abstract Cervical cancer (CESC) presents significant clinical challenges due to its complex tumor microenvironment (TME) and varied treatment responses. This study identified undifferentiated M0 macrophages as high-risk immune cells critically involved in CESC progression. Co-culture experiments further demonstrated that M0 macrophages significantly promoted HeLa cell proliferation, migration, and invasion, underscoring their pivotal role in modulating tumor cell behavior within the TME. A nine-gene prognostic model constructed from immune gene signatures highlighted CXCL8 as a key regulator of M0 macrophage behavior. Functional experiments demonstrated that CXCL8 knockdown in M0 macrophages inhibited their proliferation, shifted polarization toward an M1-dominant phenotype, and reduced tumor-promoting M2 polarization. Co-culture experiments with CXCL8-deficient M0 macrophages further revealed a suppression of HeLa cell proliferation, migration, and invasion. These findings position M0 macrophages as central regulators within the TME and suggest that targeting pathways like CXCL8 could provide novel therapeutic strategies for improving outcomes in CESC patients.